Interaction Effects of Tannic Acid and Gluten on Bread-Making and Its Starch Digestion - Seonghyeon Nam; Oguz K. Ozturk; Jongbin Lim (Foods, 2025)
In this study, we explored the binding mechanism between tannic acid (TA) and gluten to apply TA as an ingredient in bread-making to evaluate its baking performance and starch digestion. The interaction was systematically investigated by analyzing binding affinity, binding mode, and matrix structure of the TA–gluten complex using fluorescence quenching, molecular docking, and confocal laser scanning microscopy. TA strongly interacted with gluten via non-covalent interactions, mainly hydrogen bonds, and formed the major hydrogen bonds with six different glutamines (Q32, Q108, Q313, Q317, Q317, and Q349), which play a critical role in gluten network construction among amino acid residues of gluten. Additionally, TA showed lower binding affinity toward glutenin (−10.4 kcal/mol) compared to gliadin (−8.9 kcal/mol), implying stronger binding with glutenin. Consequently, the interaction between TA and gluten created a dense and compact gluten network structure. It influenced baking performance, causing a decrease in bread loaf volume while an increase in firmness and lowering the starch digestion rate, increasing slowly digestible starch and resistant starch fractions. This study identified the binding mechanism of TA toward gluten and provides better insights into how to apply TA or perhaps other polyphenols to design functional bakery products to control starch digestion rate.